Plato and Nietzsche their philosophical art - Anderson, Mark 1966- (Bloomsbury, 2014)
"It is commonly known that Nietzsche is one of Plato's primary philosophical antagonists, yet there is no full-length treatment in English of their ideas in dialogue and debate. Plato and Nietzsche is an advanced introduction to these two thinkers, with original insights and arguments interspersed throughout the text. Through a rigorous exploration of their ideas on art, metaphysics, ethics, and the nature of philosophy, and by explaining and analyzing each man's distinctive approach, Mark Anderson demonstrates the many and varied ways they play off against one another. This book provides the background necessary to understanding the principle matters at issue between these two philosophers and to developing an awareness that Nietzsche's engagement with Plato is deeper and more nuanced than it is often presented as being"--
Machine generated contents note: -- Preface AcknowledgementsConventions Introduction 1. Art and Reason2. Being 4. Becoming5. Noble and Good6. Sophia and PhilosophiaNotesBibliographyIndex
Keywords: Plato; Nietzsche, Friedrich Wilhelm / 1844-1900; Nietzsche, Friedrich -- 1844-1900; Plato -- v427-v347; PHILOSOPHY / History & Surveys / Ancient & Classical; Platonismus